Endothelial nitric oxide synthase genotype is associated with pulmonary hypertension severity in left heart failure patients. (May 2018) - Duarte, Julio D.; Kansal, Mayank; Desai, Ankit A.; Riden, Katherine; Arwood, Meghan J.; Yacob, Alex A.; Stamos, Thomas D.; Cavallari, Larisa H.; Zamanian, Roham T.; Shah, Sanjiv J.; Machado, Roberto F.
The biological mechanisms behind the development of pulmonary hypertension in the setting of left heart failure (HF-PH), including combined pre- and post-capillary pulmonary hypertension (Cpc-PH), remains unclear. This study aimed to use candidate polymorphisms in nitric oxide synthase (NOS) genes to explore the role of NOS in HF-PH. DNA samples from 118 patients with HF-PH were genotyped for the NOS3 rs1799983 and NOS2 rs3730017 polymorphisms. A multiple regression model was used to compare hemodynamic measurements between genotype groups. Patients with the T/T genotype at rs1799983 possessed a nearly 10 mmHg increased transpulmonary gradient (TPG) compared to those with other genotypes ( P  = 0.006). This finding was replicated in an independent cohort of 94 HF-PH patients ( P  = 0.005). However, when tested in a cohort of 162 pre-capillary pulmonary arterial hypertension patients, no association was observed. In a combined analysis of both HF-PH cohorts, mean pulmonary artery pressure (mPAP), diastolic pulmonary gradient (DPG), and CpcPH status were also associated with rs1799983 genotype ( P  = 0.005, P  = 0.03, and P  = 0.02, respectively). In patients with HF-PH, the NOS3 rs1799983 polymorphism is associated with TPG, and potentially mPAP and DPG as well. These findings suggest that endothelial NOS (encoded by NOS3 ) may be involved in the pulmonary vascular remodeling observed in Cpc-PH and warrants further study.